2011
DOI: 10.2140/jomms.2011.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contact surface shape on lifetime of cellular focal adhesion

Abstract: As a means of better understanding cell-matrix adhesion, we consider the effects that the contact surface shape of a cellular focal adhesion has on its adhesion lifetime. An idealized model of focal adhesion is adopted in which two dissimilar elastic media are bonded together by an array of ligand/receptor bonds modeled as Hookean springs on a curved surface. The cluster of bonds is subjected to a constant applied tensile load F, and the distribution of traction forces on the individual bonds is assumed to obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In particular, it was found that adhesion of live cells to external surfaces plays an important role in many cellular processes [3,4]. Recently, the effect of contact surface shape as a factor to control focal adhesion lifetime was studied [5], while modeling the cell and substrate as a semi-infinite elastic media.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was found that adhesion of live cells to external surfaces plays an important role in many cellular processes [3,4]. Recently, the effect of contact surface shape as a factor to control focal adhesion lifetime was studied [5], while modeling the cell and substrate as a semi-infinite elastic media.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ju et al [40] investigated the two-dimensional receptor-ligand association kinetics, which was found to be transport regulated. By recognizing that the mechanical properties of the substrate are crucial in the formation and growth of FAs, Gao and his co-workers successfully developed a coupled stochastic-elastic model [41][42][43][44] to present insights into the biophysical behaviour in cell adhesion, such as stiffness and orientation-dependent lifetime of cluster bonds [42,[45][46][47][48][49], stable size of the molecular bond cluster for cell adhesion [41,45,50], shape-dependent strength of cell adhesion [51][52][53], enhancement of cell adhesion via pre-tension in the cytoskeleton [54,55] and cell adhesion under cyclic tension [56].…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al 17,18 performed Monte-Carlo simulations to investigate the adhesion lifetime and strength of a single or periodic arrays of bond clusters between two elastic media. Wang and Gao 19 and Rizza et al 20 investigated the size-and shape-dependent pull-off force and adhesion lifetime of a bond cluster, and showed that strong and stable adhesion can be achieved by selecting an optimal surface shape, somewhat analogous to an earlier study of Gao and Yao 21 for non-specific van der Waals interaction between elastic solids.…”
mentioning
confidence: 86%